2019
DOI: 10.1017/s0007114519003076
|View full text |Cite
|
Sign up to set email alerts
|

Association of supplemental calcium and dairy milk intake with all-cause and cause-specific mortality in the UK Biobank: a prospective cohort study

Abstract: Excessive Ca intakes have been proposed to associate with vascular calcification and a higher risk of prostate cancer. We investigated the associations of supplemental and dietary Ca intake with mortality using data from 497 828 UK Biobank participants. The average follow-up was 4·2 years and 14 255 participants died, 8297 from cancer, 2959 from CVD and 572 from respiratory disease. The use of Ca supplements and milk consumption were associated with differences in mortality in younger (≤65 years) but not in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…47 Despite the recent controversy relating to the proposed risk of calcium supplementation, the most recent cross-sectional study from UK Biobank showed no association with all-cause mortality. 48 Finally, creatine has consistently shown to augment exercise-induced increases in muscle mass and strength, 49 and recent reports suggest that this nutrient may increase bone density. 49 Further research is needed to clarify the effects of creatine monohydrate in osteosarcopenic populations, particularly in respect to adaptations in bone microarchitecture using high-resolution imaging.…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Despite the recent controversy relating to the proposed risk of calcium supplementation, the most recent cross-sectional study from UK Biobank showed no association with all-cause mortality. 48 Finally, creatine has consistently shown to augment exercise-induced increases in muscle mass and strength, 49 and recent reports suggest that this nutrient may increase bone density. 49 Further research is needed to clarify the effects of creatine monohydrate in osteosarcopenic populations, particularly in respect to adaptations in bone microarchitecture using high-resolution imaging.…”
Section: Investigationsmentioning
confidence: 99%
“…Although the benefits of calcium in reducing fracture risk are equivocal, reference guidelines suggest an intake of 1000–1300 mg/day which should be met through supplementation if dietary intake is suboptimal . Despite the recent controversy relating to the proposed risk of calcium supplementation, the most recent cross‐sectional study from UK Biobank showed no association with all‐cause mortality …”
Section: Treatment: Progressive Resistance and Balance Exercises And mentioning
confidence: 99%
“…The association of milk consumption with all-cause mortality and CVD outcomes has been controversial [ 7 , 13 , 28 ]. Xu et al reported that participants with low fat milk intake indicated a decreased risk of mortality compared to participants consuming whole milk [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…One would expect increased vascular calcifications related to a diet rich in dairy products. However little evidence for harm with dietary or supplemental calcium (Ca) was reported on vascular function [100,101].…”
Section: Dietary Choices and Vascular Ageingmentioning
confidence: 99%